The legal capacity of Olympic Games participants - Jiao, H.; Cheng, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The study examines the legal status of Olympic games participants. Through this research, it was anticipated that a better understanding of the potential legal problems of the Olympic games can be achieved. Methods This article used the following methods: normative analysis and analysis review of relevant documents from historical, philosophical and cultural perspectives. Results The legal status of Olympic Games participants focuses mainly on what rights athletes will have under the related legal system during the period of the Olympic Games. The rights of athletes can be classified into fundamental rights and ordinary rights according to the differences in definition. Conclusions (1) The fundamental right of athletes: The fundamental right refers to the legal rights which athletes have under the legal system of national and international law. Specifically, athletes have human rights under the human rights laws which are established through international conventions, customary law and national law. The rights mainly include the right to life, freedom from torture, right to liberty and security, freedom of thought, freedom of expression, labor rights, freedom of belief and rights to health which should be respected, achieved and maintained. (2) The ordinary rights of athletes: Ordinary rights refer to the rights that athletes have under the system of the Olympic act, which is not a real law by nature. Therefore, ordinary rights are not legal rights, but rights in the meaning of rules. According to the different stages of the Olympic games, the ordinary rights of athletes can be classified into three types: right of entry, right to freedom contest and relief rights. Right of entry means any athlete can choose to participate or not participate in the Olympic games and in which contests, free from interference of any organization or individual. This type of right stems from the nature of the Olympic games, which has been determined by the relevant provisions of the Olympic charter. Right to freedom contest, is the most important professional right in the Olympic games. This right means every player should acquire equal treatment before the law, regardless of differences in age, nationality, race, color, or other factors. Any dispute arising on the occasion of, or in connection with, the Olympic Games shall be submitted exclusively to the Court of Arbitration for Sport, in accordance with the Code of Sports- Related. Thus, every player should have the relief rights. Through exerting their relief rights, players` entity rights can be protected. In this way, a healthy and Orderly Olympic society will be established.